Pemberdayaan Jemaat dalam Pelayanan Holistik Berbasis Pendidikan Agama Kristen di Yayasan Sola Gratia Medan - Thomson Siallagan (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Churches and Christian institutions frequently face the challenge of congregations whose understanding of ministry remains confined to the spiritual dimension alone, while the holistic ministry mandate calls for active engagement across social, educational, and economic spheres. This study examines two primary objectives: first, how Christian Religious Education (CRE) shapes congregational understanding of holistic church ministry; and second, how CRE equips congregants with the concrete capacity to serve comprehensively. A qualitative approach with a case study design was employed at Yayasan Sola Gratia Medan. Data were gathered through in-depth interviews with seven informants comprising foundation leaders, program coordinators, active church members, volunteers, and beneficiaries. Analysis followed a thematic framework encompassing data reduction, display, and conclusion drawing. Findings reveal that: (1) consistent CRE implementation at Yayasan Sola Gratia has successfully shifted the congregational ministry paradigm from exclusively spiritual to holistically transformative; and (2) congregants who have internalized CRE values demonstrate more structured ministry capacity, stronger theological motivation, and significant cross-dimensional engagement. This research contributes a contextual CRE model relevant for church-based institutions operating in multidimensional urban environments.